Hemorrhagic Thoracic Spinal Epidural Angiolipoma: A Case Report - A, Saufi; KH, Chan; Z, Zamzuri; AR, Ralib; AR, Azlina (IIUM Medical Journal Malaysia, 2014)
Spinal epidural angiolipomas are rare benign tumors. The tumors contain both vascular and mature adipose components. Typically, they present with a progressive clinical course. Acute presentation is rare. We present a case of a fifteen-year-old girl who presented with a sudden onset of backpain followed by paraparesis with bladder and bowel incontinence. Neurological examination showed sensory loss below T10 with Grade 2 motor power. Spinal MRI showed long segment extradural lesion at T6-T9 level. Multiple laminectomy and excision of the tumor containing areas of hemorrhage was performed. Histopathology report revealed angiolipoma.